INFLUENCE OF CLADDING ON CONSTRAINT EFFECT OF REACTOR PRESSURE VESSEL SUBJECTED TO PRESSURIZED THERMAL SHOCK - YANG XiaoHua; WANG ZhongXian (Jixie qiangdu)
The 3 D FE models of reactor pressure vessel（ RPV） with an axial crackwere built. The aspect ratio of the crack is a/c = 1/2（ a = 30 mm,c = 60 mm）. The elastic-plastic fracture mechanics analysis of reactor pressure vessels with different cladding thickness（ h = 0 mm,4 mm and 8 mm） subjected to pressurized thermal shock（ PTS） transients was studied. The influence of cladding thickness on integrity has been discussed by using J-A2 method and J-Qmethod. The result shows that the Jintegral on the front of crack decreases with the increasing thickness of cladding. The Q and A2 valueincreases near the interface between cladding and base material. But the maximum of Q and A2 ofcladding on the front of the crack is near the deepest point of the crack and decreases with the increasing cladding thickness.